2013
DOI: 10.5402/2013/359727
|View full text |Cite
|
Sign up to set email alerts
|

Food Value of Two Varieties of Ginger (Zingiber officinale) Commonly Consumed in Nigeria

Abstract: Ginger (Zingiber officinale) is a well-known and widely used herb, which contains several interesting bioactive constituents and possesses health-promoting properties. The proximate, mineral, antinutrient, amino acid, and phytochemical components of two varieties of ginger (Zingiber officinale) were investigated. Amino acid composition was determined using standard analytical techniques. The results obtained in percentages in the two varieties of ginger (white and yellow types) were crude fibre (21.90, 8.30), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 18 publications
5
15
2
1
Order By: Relevance
“…The phytochemical screening of the fresh rhizomes of Z. officinale revealed the presence of alkaloids, tannin, saponins, phlobatannins, flavonoids, anthraquinones, steroids, terpenes, cardenolides, phenols and cardiac glycosides although in varying quantities. These results were in agreement with results reported by [24] and [25].…”
Section: Discussionsupporting
confidence: 94%
“…The phytochemical screening of the fresh rhizomes of Z. officinale revealed the presence of alkaloids, tannin, saponins, phlobatannins, flavonoids, anthraquinones, steroids, terpenes, cardenolides, phenols and cardiac glycosides although in varying quantities. These results were in agreement with results reported by [24] and [25].…”
Section: Discussionsupporting
confidence: 94%
“…Krejpcio et al (2007) reported that the content of zinc concentration of spices in Polish markets is found to be 5.96 to 16.95 mg/kg which is higher than results obtained in this work. The mean concentration of zinc determined in this study is lower than the value determined in India (Devi et al, 2008) but greater than the value obtained (0.03-0.04 mg/kg) in Nigeria (Ajayi et al, 2013). The content of zinc in ginger sample of the current study (Ethiopia) is less than the permissible limit set by WHO/FAO (2011) in edible plants (50 mg/kg).…”
Section: Zinc (Zn)contrasting
confidence: 81%
“…Ginger contains several compounds and its major components are 6-gingerol, 6shogaol, and 6-paradol that possess strong antioxidant activity (Prasad and Tyagi, 2015) and it possesses health benefits. Ginger also contains different nutrients such as protein, fats, insoluble fibers, soluble fibers, carbohydrates and vitamins (Shirin and Jamush, 2010;Ajayi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, dietary supplementation with ginger rhizomes restores the level of NO in hypertensive rats. This increase in NO could be a result of the fact that ginger rhizomes exhibited inhibitory effect on arginase activity or by increasing endogenous L-arginine level through dietary means as reported by Ajayi, Akomolafe, and Akinyemi (2013).…”
Section: Discussionmentioning
confidence: 82%